Does Protection of Marine Areas Safeguard Coral Reefs From Human-Source Pollution? - Kaimba, Alphaxand; de Villiers, Santie; Wambua, Sammy (Frontiers in Environmental Science, 2019)
Abstract Marine biodiversity is under increasing threat as the area covered by corals diminishes under pressure from climate change and human activities, most of which lead to marine pollution. In Kenya, marine protected areas (MPAs) are the key strategy used to protect coral reefs and biodiversity. However, MPAs’ effectiveness to prevent pollution of the reefs has not been specifically assessed. We determined if the levels of surrogates of human-source pollution, i.e. E. coli and nutrient concentrations on Kenyan coral reefs, varied with increasing levels of marine protection at the Kilifi creek (least protection), Malindi Reserve (moderate protection) and Kuruwitu Conservancy (strictest protection). The most probable number (MPN) of E. coli was estimated by serial dilution while nitrate and orthophosphate concentrations were determined spectrophotometrically. As protection increased from “least”, to “moderate” and “strictest”, E. coli concentrations (MPN/100 mL) decreased from 29, to 16 and undetectable, while mean orthophosphate concentrations increased from 0.326, to 0.422, and 0.524 mg/L, respectively. Mean nitrate concentrations, on the other hand, showed no trend with protection. These results suggest the potential of marine protection to mitigate coral reef pollution, especially from microbes. They also point to the possibility that multiple sources of pollution exist on which marine protection may have little or no effect. Significantly, this pilot study points to the need for improved study design to definitively determine role MPAs may play in protecting against pollution.